The Optical Effect of Thermal Expansion over Excessed Injection Molded Lens Arrays in Modern LED Outdoor Luminaires - Zsellér, Viktor; Samu, Krisztián (Recent Innovations in Mechatronics, 2016)
For the rapid development observable in solid state lighting technology, both in favor of the better lighting performance achievable and the advantage in upkeep, changing the conventional installations to LED luminaires is often considerable in the modern roadway lighting practice. By these modernization investments the sales volume is usually high for lower additional expenses and a quicker RoI; thus the replacement products are generally cost sensitive. As the global market price of Aluminum increases on a long term trend, while the cost of the task efficient luminous power became very desirable with Light Emitting Diode; a high level of integration and compactness is demanded by such luminaire designs. This approach raises complex technical challenges, as the thermal expansion difference between the lens array and the Insulated Metal Substrate (IMS) Printed Circuit Board can lead to major deviation in the light distribution over the rated ambient temperature range. Having a robust design is a key aspect in providing a reliable, safe lighting design for any application of a global product.